Trimetazidine-Induced Parkinsonism: A Systematic Review - Dy, Anna Marielle B.; Limjoco, Lorenzo Luis G.; Jamora, Roland Dominic G. (Frontiers in Neurology, 2020)
Importance: Trimetazidine (TMZ) is a medication given for patients with stable coronary artery disease. While it is reportedly well-tolerated, there are increasing reports of adverse events such as parkinsonism. Objectives: The purpose of this study was to systematically review the current available literature on TMZ-induced parkinsonism. Evidence Review: A search of Scopus, MEDLINE, EMBASE, The Cochrane Library, Health Technology Assessment Database, PubMed, Science Direct and Google Scholar was conducted on or before November 7, 2019. The literature search included cohort studies, prospective and/ or retrospective studies, meta-analysis and other systematic reviews published as an original article including abstracts and full-texts. We included patients taking TMZ who developed one or more of the following parkinsonian symptoms: bradykinesia, tremors, rigidity, postural instability, which improved after withdrawal of the said medication. Findings: There are currently 5 studies on TMZ use and associated parkinsonism. The literature included 2 case reports, 1 case series, 1 retrospective and 1 prospective study. We found no results from randomized clinical trials. Overall, 88 patients developed TMZ-induced parkinsonism. Regression of parkinsonism was reported in all of the participants after withdrawal of TMZ. A total of 49 patients (55.7%) had complete regression of symptoms while 39 patients (44.3%) had significant reduction of symptoms. The duration between TMZ (dose, 60-80 mg/ day) intake and onset of symptoms ranged from 4 months to 20 years. The most commonly reported extrapyramidal symptoms were akinesia, rigidity, postural disturbances and gait disorders, which were usually mild and symmetric. Conclusions and Relevance: The current literature suggests that TMZ can induce parkinsonism which is reversible with drug withdrawal. It is warranted to examine patients, especially the elderly on TMZ for parkinsonian symptoms and those with pre-existing neurodegenerative diseases. Further studies are needed to assess the risk-benefit ratio of this drug especially in the elderly age group.